Synchronous multiple primary malignancies of clear cell renal cell carcinoma with sarcomatoid, thyroid carcinoma: a case report - Tan, Yaxian; Chen, Xiaowen; Ye, Mushi; Li, Xiaofang; Liu, Wenci; Liao, Sihai; Xie, Zhong; Zuo, Yufang (Frontiers in Oncology, 2023)
Multiple primary malignant neoplasms (MPMNs) are defined as the presence of two or more malignancies with different histologies in the same patient. MPMNs are rare, accounting for fewer than 4% of all tumor cases. Depending on the time interval between the diagnosis of the different malignancies, they are classified as either simultaneous or metachronous MPMNs, with simultaneous being rarer in multiple primary malignant neoplasms. Here we present a 63-year-old female patient presenting with multiple primary renal and thyroid carcinomas and discuss the risk factors, treatment options, and prognosis of rare dual carcinomas. Conclusion: We focus on managing multidisciplinary teams and selecting individualized treatment options to deliver valuable treatment strategies to patients.